ANTIOXIDANT AND NEUROPROTECTIVE EFFECTS OFLEUCAS INDICAON IRON INDUCED LIPID PEROXIDATION IN RAT BRAIN IN VITRO - T. RAVI KIRAN (International Journal of Pharma and Bio Sciences, 2016)
Neurodegenerative diseases have been linked to oxidative stress arising from peroxidation of membrane biomolecules and high levels of iron have been reported to play an important role in neurodegenerative diseases. The present study compares the antioxidant and neuroprotective effects of aqueous and methanolic extract of Leucasindica(L.indica)on iron induced lipid peroxidation in rat’s brain in vitro. The total phenol,total flavonoids, vitamin C content,reducing property and hydroxyl radical scavenging ability were determined. 4-hydroxy isopthalic acid was the major phenoliccompound identified by HPLC-VWD analysis. The results of the study revealed that methanolic extract of L. indica had significantly higher vitamin C, flavonoid content, reducing power and DPPH scavenging ability than the Aqueous extract. However, both extracts significantly inhibited (p<0.05) Fe(II) induced lipid peroxidation in the rat brain in a dose-dependent manner. In conclusion, the methanolic extract was more potent inhibitor of lipid peroxidation in the rat’sbrain and this is probably due to its higher phenol content and reducing power.